HPRT and Purine Salvaging Are Critical for Hematopoietic Stem Cell Function. (12th October 2019) - Vogel, Mona; Moehrle, Bettina; Brown, Andreas; Eiwen, Karina; Sakk, Vadim; Geiger, Hartmut
Abstract: Adult hematopoietic stem cells (HSCs) maintain tissue homeostasis and regenerative capacity of the hematopoietic system through self-renewal and differentiation. Metabolism is recognized as an important regulatory entity controlling stem cells. As purine nucleotides are essential for metabolic functions, we analyzed the role of hypoxanthine guanine phosphoribosyl transferase (HPRT)-associated purine salvaging in HSCs. Here, we demonstrate that hematopoietic stem and progenitor cells (HSPCs) show a strong dependence on HPRT-associated purine salvaging. HSPCs with lower HPRT activity had a severely reduced competitive repopulation ability upon transplantation. Strikingly, HPRT deficiency resulted in altered cell-cycle progression, proliferation kinetics and mitochondrial membrane potential primarily in the HSC compartment, whereas more committed progenitors were less affected. Our data thus imply a unique and important role of HPRT and the purine salvage pathway for HSC function. Stem Cells   2019;37:1606–1614 : Abstract : Free purine bases are recycled by the purine salvaging enzyme hypoxanthine guanine phosphoribosyl transferase (HPRT) (left). A reduced activity of HPRT alters cell-cycle progression and function of mitochondria (right) in hematopoietic stem cells (HSCs), which is linked to reduced HSC repopulation ability upon transplantation. Our data suggest that an elevated level of purine degradation products might initiate these phenotypes in HSCs in which HPRT activity is reduced.